Phyllanthus novofriburgensis and P. pedrosae, two new species of Phyllanthus subsect. Clausseniani (Phyllanthaceae) from Southeastern Brazil - Mendes, Jone Clebson Ribeiro; Braga, João Marcelo Alvarenga; Fraga, Claudio Nicoletti de; Athiê-Souza, Sarah Maria (European Journal of Taxonomy, 2024)
Phyllanthus novofriburgensis J.C.R.Mendes, J.M.A.Braga & Fraga sp. nov. and P. pedrosae J.C.R.Mendes, J.M.A.Braga & Fraga sp. nov. are new species of Phyllanthaceae described from the Brazilian Atlantic Forest and Brazilian Cerrado, respectively. Phyllanthus novofriburgensis resembles P. acutifolius Poir. ex Spreng., P. hypoleucus Müll.Arg. and P. lilliputianus J.C.R.Mendes, J.M.A.Braga & Fraga, sharing ovate, elliptical, and lanceolate leaf blades. However, it can be distinguished by its pendulous habit, often with sinuous branches and lanceolate leaf blades with characteristically revolute margins. Phyllanthus pedrosae exhibits morphological similarities with P. claussenii Müll.Arg. due to its subshrubby and prostrate habit. It is distinghuished by the unisexual inflorescence with cymules composed of one or two staminate flowers proximally positioned in the axil of the branches and solitary pistillate flowers distally situated, and the 5-merous calyx in the staminate and pistillate flowers. Both new species are classified in Phyllanthus subgen. Phyllanthus sect. Phyllanthus subsect. Clausseniani G.L.Webster, primarily due to the deeply emarginate anthers. Notes on their geographical distribution and habitat are provided, as well as a key to the species of Phyllanthus from Southeastern Brazil.